Researching Waqf Forest Studies - Sri (SMART Insight, 2021)
This research aims to identify and map research related to the development of research trends in Waqf Forest. The data analyzed are articles published by leading journals from 1986 to 2021. The number of articles analyzed is 70 articles indexed by Scopus. The research methods are descriptive statistical methods and bibliometric analysis. The results of the study show that the number of articles discussing the theme of Waqf Forest shows an increasing trend starting from 2005. Popular keywords used are environment, sustainability, and waqf. The most prolific writers are Hashim J, Hashim H, and Abidin IZ, while the country with the most popular writers and the most in the United States. This research provides information for researchers who focus on research in the field of Waqf Forest.